AN ANALYSIS REFLECTION ABOUT SYNCHRONOUS LEARNING USING ZOOM MEETING FOR EFL UNIVERSITY STUDENTS OF UIN SU MEDAN IN ONLINE LEARNING DURING COVID-19 PANDEMIC - Yana Hudriyah (UIN Sumatera Utara, 2022)
This study aimed to find the reflection about synchronous learning using Zoom Meeting for EFL university students of UIN SU Medan in online learning during Covid-19 Pandemic. This study used qualitative research with descriptive method. The data was collected through interviews. The participants of this research were ten EFL university students of UIN SU Medan. The result of this study are presented descriptively to reveal the students’ reflections of Zoom Meeting comprehensively. The results of this study show that english online learning through Zoom Meeting has some benefits for students in their learning namely listening, reading and speaking, and students also faced some obstacles while using Zoom Meeting as an online learning medium.